Potential Applications of Frass Derived from Black Soldier Fly Larvae Treatment of Food Waste: A Review - Noor Ezlin Ahmad Basri; Nur Asyiqin Azman; Irfana Kabir Ahmad; Fatihah Suja; Nurul Ain Abdul Jalil; Nur Fardilla Amrul (Foods, 2022)
The disposal of large amounts of food waste has caused serious environmental pollution and financial losses globally. Compared to alternative disposal methods (landfills, incineration, and anaerobic digestion), composting by black soldier fly larvae (BSFL) is a promising alternative for food waste management. Despite extensive research into larval biomass, another valuable by-product generated from BSFL composting is BSFL frass. However, limited information is available for its potential application. The applications of BSFL frass can be intensified by understanding its physicochemical characteristics, benefits, and challenges of BSFL frass derived from food waste. BSFL frass is harvested after 9–23 days of the experiment, depending on the substrate used in the composting process. The generated BSFL frass could exceed 33% of the original weight of the substrate. The physicochemical characteristics of BSFL frass are as follows: the temperature after harvest is 24 °C to 27 °C, pH is 5.6–8.0, moisture content is 30 to 72%, C/N ratio is 8:1 to 27:1, high nitrogen, phosphorus, and potassium (NPK) content, and low heavy metal content. This paper reviews the characteristics, benefits, and application of BSFL frass. It will also investigate the challenges of using food waste substrates to produce BSFL frass, as well as the best way to pre-treat the food waste substrate and post-treat the BSFL frass.